Suicidal behaviour and quality of life in Slovene prisons - Zadravec Šedivy, Nuša (The journal of forensic psychiatry & psychology, 2021)
Prisoners are an extremely vulnerable group regarding suicidal behaviour, with a consistently higher prevalence of suicide when compared to the general population. However, the characteristics of suicidal behaviour for this group are understudied in Slovenia. We wanted to investigate the characteristics of suicidal behaviour and suicide-related factors in male prisoners of this country and recruited 419 male prisoners. These individuals filled-in a package of questionnaires which included demographic characteristics, medical history, WHOQOL-BREF, Five Well-Being Index, Paykel’s questions on suicidal behaviour, Depression, Anxiety and Stress Scale, and the Interpersonal Needs questionnaire. Study results showed that 10.3% of participants reported being at current risk for suicide, with these inmates reporting more severe mental health problems, lower quality of life and lower well-being levels. Lack of social contacts did not affect mental health as much as the quality of social support, where perceived belongingness and acceptance by others represented a protective factor for suicidal behaviour.